Comparative analysis of survival rates as applied to treated breast cancer cases. - Sanvictores, Ma. Elinor G.
2 methods of survival time analysis were demonstrated in this study: the modified life table technique and log rank test. The data which were obtained by reviewing the records of the Filipino female patients with clinical stage II breast cancer treated at the U.P. - P.G.H. Medical Center were used in illustrating the application of these methods. The subjects were categorized according to the mode of mastectomy they underwent, i.e., radical and modified radical, and the patients in each group were further classified according to age groups, i.e. 45 and 45 years old. Results of the life table analyses, as visualized from the graphs, indicate a higher survival trend among the patients who underwent modified radical mastectomy and among the older patients most of whom were postmenopausal at the time of operation. Whereas, the log-rank test was unable to demonstrate a statistically significant difference in the survival times of patients classified according to mode of treatment, a statistically significant difference was shown by the same test using age as the prognostic factor. At this juncture, it is important to note that the results of this study are inconclusive in as much as no randomization has been done in the allocation of treatments among the breast cancer patients.
Thesis (MS Public Health, Biometry)--University of the Philippines Manila.
Keywords: Breast cancer; Survival analysis (biometry).; Mastectomy